-2x+6x+26=3x-22

Simple and best practice solution for -2x+6x+26=3x-22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+6x+26=3x-22 equation:



-2x+6x+26=3x-22
We move all terms to the left:
-2x+6x+26-(3x-22)=0
We add all the numbers together, and all the variables
4x-(3x-22)+26=0
We get rid of parentheses
4x-3x+22+26=0
We add all the numbers together, and all the variables
x+48=0
We move all terms containing x to the left, all other terms to the right
x=-48

See similar equations:

| 2(p-4)=2 | | 6b^2=b^2+7-b | | 4(x-5)+4x=-24+2x | | h=16^2+48+3 | | 6(t-88)=24 | | −2+5x=4x+2 | | h+72/2=3 | | 3=j/3-5 | | 3x+6-4x=24+5x | | s+6/9=3 | | 5(g-74)=90 | | 70+35h=1 | | q+27/9=7 | | 6=z-56/7 | | 2b=5=19 | | 3=−15c+8 | | 50-2x=24 | | 9x/4=6 | | 2x+36-16=16x | | 6n+11=7+4(1+8n) | | 9t+3=6t+15 | | x(-7)=63 | | 2(1+b)=-7+5b | | 5-3x-3=25 | | 8-1.8=1.2x | | -3-7(2+4x)=95 | | 3(l+6)=39 | | (2x+3)=(4x+20) | | 2g-g+4=17 | | 28*9=18+-2x | | 64=4f | | 4-2n=16. |

Equations solver categories